Global Perspectives on Social Media and Language Evolution - Hartina, St.; Rivia, Dian (Lingua : Journal of Linguistics and Language, 2024)
Social media has become a transformative force in global communication, accelerating processes of linguistic change in unprecedented ways. This review aims to synthesize current research on how digital platforms reshape language through neologisms, semantic shifts, non-standard grammar, and sociolinguistic dynamics. A systematic search was conducted across databases including Scopus, Web of Science, JSTOR, and Google Scholar, using targeted keywords and rigorous inclusion criteria. Studies employing both qualitative and quantitative methods were analyzed to capture a comprehensive picture of digital language evolution. Results indicate that platforms such as Twitter, TikTok, and Reddit foster distinctive forms of linguistic innovation shaped by technological affordances and community practices. Neologisms and acronyms emerge rapidly, semantic changes redefine meanings of common words, and syntactic flexibility challenges traditional norms. Sociolinguistic factors, particularly age and community identity, drive adoption, while systemic influences such as globalization and digital connectivity accelerate diffusion. These findings highlight not only the creative adaptability of language but also the challenges posed by polarization and the erosion of traditional registers. The discussion emphasizes the need for inclusive language policies, translanguaging pedagogy, and teacher training to address these shifts. Limitations in current research include insufficient focus on syntax, underrepresentation of non-Western contexts, and methodological challenges in analyzing unstructured digital data. Future research should address these gaps to enhance understanding of digital linguistics. By situating social media as both a mirror and catalyst of linguistic change, this study underscores its central role in shaping communication in the twenty-first century.